2009
DOI: 10.1002/uog.6415
|View full text |Cite
|
Sign up to set email alerts
|

Adding a single CA 125 measurement to ultrasound imaging performed by an experienced examiner does not improve preoperative discrimination between benign and malignant adnexal masses

Abstract: Objectives To determine whether CA 125 measurement is superior to ultrasound imaging performed by an experienced examiner for discriminating between benign and malignant adnexal lesions, and to determine whether adding CA 125 to ultrasound examination improves diagnostic performance.Methods This is a prospective multicenter study (International Ovarian Tumor Analysis (IOTA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 30 publications
6
59
2
3
Order By: Relevance
“…We observed much higher CA-125 levels in endometriomas, abscesses, and fibromas than in other benign masses, and much lower levels in borderline tumors than in invasive tumors, with only stage II-IV invasive cancers having consistently elevated CA-125 levels (9). We found that the subjective assessment of the ultrasound image of an adnexal mass by an experienced ultrasonographer was superior to serum CA-125 for the diagnosis of malignancy and that adding information on the CA-125 level to subjective evaluation of ultrasound images did not improve diagnostic performance (8,20,21). Moreover, CA-125 appeared to be replaceable by other variables in mathematical models developed to predict malignancy in adnexal masses (19).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We observed much higher CA-125 levels in endometriomas, abscesses, and fibromas than in other benign masses, and much lower levels in borderline tumors than in invasive tumors, with only stage II-IV invasive cancers having consistently elevated CA-125 levels (9). We found that the subjective assessment of the ultrasound image of an adnexal mass by an experienced ultrasonographer was superior to serum CA-125 for the diagnosis of malignancy and that adding information on the CA-125 level to subjective evaluation of ultrasound images did not improve diagnostic performance (8,20,21). Moreover, CA-125 appeared to be replaceable by other variables in mathematical models developed to predict malignancy in adnexal masses (19).…”
Section: Introductionmentioning
confidence: 76%
“…The International Ovarian Tumor Analysis (IOTA) study group has previously investigated the role of CA-125 in the preoperative assessment of adnexal masses (9,19,20). We observed much higher CA-125 levels in endometriomas, abscesses, and fibromas than in other benign masses, and much lower levels in borderline tumors than in invasive tumors, with only stage II-IV invasive cancers having consistently elevated CA-125 levels (9).…”
Section: Introductionmentioning
confidence: 77%
“…18 Another recent study comparing CA-125 alone versus ultrasound with or without CA-125 found that CA-125 did not increase the detection of cancer compared with ultrasound alone. 19 Randomized data do not yet support routine screening for ovarian cancer in the general population, and routine screening is not currently recommended by any professional society. 8,20 Some physicians monitor women with high-risk factors (e.g., BRCA mutations, a family history) using CA-125 levels and endovaginal ultrasound; however, prospective validation of these tests remains elusive.…”
Section: Screeningmentioning
confidence: 99%
“…Emphasizing morphologic characteristics of the adnexal masses, in so called pattern recognition, features like presence of mixed consistency or multilocular components, septa or excrescence could differentiate benign from malignant neoplasms [5][6][7]. This pattern recognition of adnexal masses reach a sensitivity of 86% and specificity of 80% when is performed by non-expert ultrasound examiner, and when performed by experienced one it has sensitivity of 90% and specificity of 93% [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, all these new models for malignancy prediction have yet to be confirmed in future studies. Therefore, the most common approach to estimate the likelihood of ovarian malignancy in daily practice is still the use of ultrasound examination as a first-stage, and the serum CA-125 combined with HE4 as a second-stage tool [6,15].…”
Section: Introductionmentioning
confidence: 99%